The Essence of Software Engineering 2018
DOI: 10.1007/978-3-319-73897-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Towards Deviceless Edge Computing: Challenges, Design Aspects, and Models for Serverless Paradigm at the Edge

Abstract: Recently, Cloud Computing, Edge Computing, and the Internet of Things (IoT) have been converging ever stronger, sparking creation of very large-scale, geographically distributed systems [1, 2]. Such systems intensively exploit Cloud Computing models and technologies, predominantly by utilizing large and remote data centers, but also nearby Cloudlets [3, 4] to enhance resource-constrained Edge devices (e.g., in terms of computation offloading [5-7] and data staging [8]) or to provide an execution environment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…With specific reference to edge computing environments, in [25] the authors propose an abstraction called Software-Defined Gateway, which hides the complexity of local IoT devices and offers a clean API for the integration with widely adopted serverless platforms; they focus on the DevOps aspects, and mention the issue of "scheduling [the] functions execution on loosely coupled and scarce edge resources" as an open research issue, which we address in this work. In [12] the authors take a more radical approach and assume that every edge node may decide at the same time where to route every incoming task (at a network-level) and which node has to execute the remaining processing, where applications are assumed to be modeled as directed computation graphs.…”
Section: State Of the Artmentioning
confidence: 99%
“…With specific reference to edge computing environments, in [25] the authors propose an abstraction called Software-Defined Gateway, which hides the complexity of local IoT devices and offers a clean API for the integration with widely adopted serverless platforms; they focus on the DevOps aspects, and mention the issue of "scheduling [the] functions execution on loosely coupled and scarce edge resources" as an open research issue, which we address in this work. In [12] the authors take a more radical approach and assume that every edge node may decide at the same time where to route every incoming task (at a network-level) and which node has to execute the remaining processing, where applications are assumed to be modeled as directed computation graphs.…”
Section: State Of the Artmentioning
confidence: 99%
“…1,10,12,122 Notably, the finely-grained execution units of serverless functions can lead to high load on central scheduling components, as Rausch et al 123 have shown in comparison to their earlier work. [124][125][126] The authors claim that there is no technical solution that is able to handle such scheduling of function execution across edge, intermediaries, and the cloud. On the other hand, precisely this flexible scheduling of function executions can maximize resource allocation and lead to better auction conditions for both providers as well as consumers.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, existing research has not taken into account the unique challenges and opportunities of fog‐based FaaS platforms, although it has been shown that the FaaS paradigm is a good fit for fog applications 1,10,12,122 . Notably, the finely‐grained execution units of serverless functions can lead to high load on central scheduling components, as Rausch et al 123 have shown in comparison to their earlier work 124‐126 . The authors claim that there is no technical solution that is able to handle such scheduling of function execution across edge, intermediaries, and the cloud.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, existing research has not taken into account the unique challenges and opportunities of fog-based FaaS platforms, although it has been shown that the FaaS paradigm is a good fit for fog applications [103,104,122,20]. Notably, the finely-grained execution units of serverless functions can lead to high load on central scheduling components, as Rausch et al [108] have shown in comparison to their earlier work [90,89,109]. The authors claim that there is no technical solution that is able to handle such scheduling of function execution across edge, intermediaries, and the cloud.…”
Section: Related Workmentioning
confidence: 99%